Land Degradation - Lal, Rattan (2015)
IFPRI Policy Seminar “Economics of Land Degradation and Improvement--A Global Assessment for Sustainable Development” held on December 3, 2015. Presentation by Rattan Lal, Carbon Management and Sequestration Center.